2013
DOI: 10.1111/tbed.12206
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of Zoonotic and Production Limiting Pathogens in Rusa Deer (Cervus timorensis rusa) from Mauritius

Abstract: Summary A population of approximately 70 000 rusa deer (Cervus timorensis russa) represents the most important mammal species reared for food on the island of Mauritius, being the main source of red meat for the local population. However, very limited information is available on the circulation of pathogens affecting the productivity and health of this species. To produce baseline data on the circulation of infectious pathogens in rusa deer under production, a serological survey and/or direct pathogen detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Moreover, these animals have been also indicated as reservoir for Leptospira spp. (JORI et al, 2014). A serological comparison between two distinct pampas deer populations showed that there was no exposure to Leptospira spp.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these animals have been also indicated as reservoir for Leptospira spp. (JORI et al, 2014). A serological comparison between two distinct pampas deer populations showed that there was no exposure to Leptospira spp.…”
Section: Introductionmentioning
confidence: 99%
“…These results can be interpreted in the context of the world's vast territory with different countries having different characteristics during summer. Meta-analyses showed that the incidence rates of Brucella in cattle and deer were higher in hotter and more humid areas (81,82). Therefore, we speculate that a similar phenomenon occurs in pigs with brucellosis.…”
Section: Discussionmentioning
confidence: 68%
“…The virus continues to expand its range across Africa countries and into new regions within endemic countries [59,159]. It should be noted that among studies that were technically excluded from our review, there were several completely negative serosurveys of animals performed in Spain [52], the Canary Islands [53], Mauritius [160], Zanzibar [161], South Korea [55], and Poland [54]. Expansion of RVFV transmission has been aided by livestock movement [34,[162][163][164][165] and the increasing frequency of extreme weather events involving heavy rainfall and flooding [60].…”
Section: Discussionmentioning
confidence: 99%